(untitled) (Research, Society and Development, 2022)
Myxosarcomas are malignant mesenchymal neoplasms that commonly affect skin and subcutaneous tissue in the trunk and limbs, and are not common in cats. Therefore, this study aims to report a case of myxosarcoma in the inguinal region of a feline, emphasizing its topographic location, as well as its clinicopathological findings. The patient arrived for care at the Veterinary Hospital of the Passo Fundo University, complaining of intermittent claudication in the right thoracic limb, and the presence of a nodule in the inguinal region – both with rapid evolution. Aspiration cytology of the nodule showed a result suggestive of a soft tissue sarcoma. He also performed laboratory and imaging tests to rule out possible metastases in the lungs and in the limb in which he had claudication and was then referred for surgical excision. The nodule was referred for histopathological examination with a confirmatory result for myxosarcoma. Due to local recurrence after surgery, the non-performance of adjuvant therapies for tumor control due to the tutor’s personal issues, and the general health status of the patient with the presence of intense pain, the feline was euthanized. Thus, it is concluded that myxosarcomas can present in any part of the body, commonly presenting local recurrences after removal and a low life expectancy. Furthermore, it is emphasized that the correlation between clinical presentation, cytology, histopathology and imaging tests further emphasize that cytology should be performed in all patients with cutaneous and subcutaneous nodules before undergoing any therapeutic procedure.